Main theoretical approaches of the creative industries: From a meta-analytical orientation (Revista de Investigaciones Universidad del Quindío, 2022)
The purpose of this article is a systematic review of the literature, appealing to recent bibliometric studies that point to research studies in Creative Industries, from management 2017 to April 2022, with a sample of journals from the Web of Science database based on a meta-analytical study of a number of 549 selected articles, was carried out with the help of the Vosviewer Software, identifying the most relevant journals and the most cited authors. Through a co-citation analysis, the authors related to the theoretical approaches were selected, which allows to build and define a theoretical path of the creative industries. Two groups of theoretical approaches were identified as results from the most cited 177 authors that converge to the creative/cultural classes approach and the media and culture approach in society.
Keywords: Creative Industries; Cultural Industries; Theoretical Approach; Meta- Analytics; Bibliometrics